LUDRUK: MASIHKAH RITUS MODERNISASI? - Kathleen Azali (Lakon : Jurnal Kajian Sastra dan Budaya, 2012)
Ludruk is a traditional folk-show drama from East Java, whose actors, producers and spectatorsgenerally come from the working class, with stories closely related to their daily life. In 1960s, whenJames L. Peacock did his extensive research, ludruk was at the peak of its “golden age”, which heregarded as “rites of modernization”. However, during the New Order era, ludruk lost its political,social and financial supports. Revival attempts thus far, amidst the boom of economic developmentand other forms of entertainment, have not been particularly successful. This paper attempts tosketch a historical background based mostly on literature reviews and field visits to ludruk shows toanalyze its relevance in contemporary Surabaya.